Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd006602.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody for reducing the risk of respiratory syncytial virus infection in children

Abstract: Background Respiratory syncytial virus (RSV) is one of the most important viral pathogens causing acute respiratory infections, resulting in about 3.4 million hospitalisations annually in children under five. Palivizumab is the only product approved for prevention of serious RSV disease, as motavizumab is no longer being developed for this condition. The efficacy and safety of palivizumab has been evaluated in randomized controlled trials (RCTs) and a large number of economic evaluations (EEs) have tested its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Bronchiolitis is a combined upper and lower respiratory tract infection resulting in increased airway secretions, and bronchospasm causing shortness of breath and wheeze. Mild cases can be nursed at home, but 2%–3% may be admitted to hospital 6 7. National Institute for Health and Care Excellence guidelines for bronchiolitis detail what to consider when assessing individuals and their need for hospital care (see table 1).…”
Section: What Is Rsv and What Does It Do?mentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchiolitis is a combined upper and lower respiratory tract infection resulting in increased airway secretions, and bronchospasm causing shortness of breath and wheeze. Mild cases can be nursed at home, but 2%–3% may be admitted to hospital 6 7. National Institute for Health and Care Excellence guidelines for bronchiolitis detail what to consider when assessing individuals and their need for hospital care (see table 1).…”
Section: What Is Rsv and What Does It Do?mentioning
confidence: 99%
“…Other countries, such as Italy and USA include attendance at community settings or cohabitees younger than 5 years as risk factors 7. Other risks may include parental smoking, day care attendance, overcrowding, being fed formula rather than breast milk, male sex, lower socioeconomic class and admission to hospital during the RSV season 3 6 11…”
Section: What Options Are Currently Available For Prophylaxis and Prementioning
confidence: 99%
“…A recent Cochrane systematic review analysed data from three RCTs (including those described above) comparing palivizumab with placebo (n=2831) and four RCTs comparing palivizumab with motavizumab (n=8265), among infants born preterm, with congenital heart disease or chronic lung disease 18. They concluded that prophylaxis compared to placebo was associated with a 51% reduction in risk of RSV hospitalisation (RR=0.49 95% CI 0.37 to 0.64) and a 50% reduction in admissions to intensive care units (RR=0.50 95% CI 0.30 to 0.81).…”
Section: Efficacy Of Palivizumabmentioning
confidence: 99%
“…They concluded that prophylaxis compared to placebo was associated with a 51% reduction in risk of RSV hospitalisation (RR=0.49 95% CI 0.37 to 0.64) and a 50% reduction in admissions to intensive care units (RR=0.50 95% CI 0.30 to 0.81). In addition, pooled analysis revealed a reduction in all-cause mortality, though this was statistically non-significant (RR=0.69 95% CI 0.42 to 1.15) 18. It is perhaps most useful though to consider the number of children that need to be treated to prevent a hospital episode.…”
Section: Efficacy Of Palivizumabmentioning
confidence: 99%
See 1 more Smart Citation